The Yehud stamp impressions : a corpus of inscribed impressions from the Persian and Hellenistic periods in Judah - Lipschitz, Oded (Eisenbrauns, 2011)
The study of the yehud stamp impressions, which appear on the handles or bodies of store jars, has persisted for over a century, beginning with the discovery of the first of these impressions at Gezer in 1904. Nevertheless, until the pioneering work of Stern in 1973, who cataloged, classified, and discussed the stamp impressions known up to 1970, discovery and publication of new stamp impressions were scattered, and analysis was cursory at best. Furthermore, a gap in research has persisted since then.Now, Oded Lipschits and David Vanderhooft are pleased to present a comprehensive catalog (through the winter of 2008-9) of published and unpublished yehud stamp impressions, with digital photographs and complete archaeological and publication data for each impression. This long-overdue resource provides a secure foundation for general reflection on the whole corpus and illuminates more-narrow fields such as stratigraphy, paleography, administration, historical geography, and Persian-period economic developments within Yehud. The catalog clarifies what is nebulous apart from a complete corpus, matters such as distribution, petrographic analysis of the clay, new readings of the seal legends, use of the toponym yehud, and significance of the title phwa. The scope of this catalog renders it a worthwhile tool for all future study of these invaluable artifacts and the period of history that produced them.